The Application of Management Information Systems in Improving Application-Based Work Effectiveness : Penerapan Sistem Informasi Manajemen dalam Meningkatkan Efektivitas Kerja Berbasis Aplikasi - Mujib, Wahyu Abdul; Kusuma, Yanda Bara (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The development of digital technology requires companies to optimize their work systems through digitalization, including in the management of human resources administration. Specific Background: Before the arrival of the My Japfa application, attendance, leave, and official leave processes were still carried out manually, which often took a long time and was prone to recording errors. Knowledge Gap: Previous studies have focused on management information systems in the education and public sectors, while studies in the agribusiness sector are still limited, particularly regarding the implementation of internal applications integrated with employees' daily activities. Aim: This study aims to analyze the implementation of the My Japfa application at PT J Gedangan Unit and assess its impact on employee work effectiveness and the role of the HR department. Results: Interviews, observations, and documentation show that this application speeds up attendance, leave, and permit processes, increases transparency, and reduces manual administrative burdens. Employee work effectiveness has increased because attendance waiting times have been reduced and data is recorded more accurately. However, obstacles such as unstable internet connections and the adaptation of senior employees remain challenges. Novelty: This study shows how the digitization of administration in the agribusiness sector can transform the role of HR from administrative to strategic, a perspective that has rarely been raised in previous studies. Implications: These findings show that the implementation of internal digital applications not only improves efficiency but also builds a more transparent and adaptive work culture. This can be a reference for other companies in adopting similar systems. Highlights: The My Japfa application improves HR administrative efficiency and employee work effectiveness. The main obstacles include the digital literacy of senior employees and network stability. Digitalization provides opportunities for HR to become more strategic. Keywords : Management Information System, Work Effectiveness, Application